'To activists: Please post and share your story': Renewing understandings on civic participation and the role of Facebook in the Indignados movement. (December 2017) - Papa, Venetia
The global upsurge in protest, which has accompanied the current international financial crisis, has highlighted the extensive use of online social media in activism, leaving aside the extent to which citizenship is enacted, empowered and potentially transformed by social media use within these movements. Drawing on citizenship and communication theories, this study employs a cross-country analysis of the relationship between citizenship, civic practices and social media within the Indignados movement in Greece and France. By the use of semi-structured interviews, we attempt to discern the degree of involvement of actors with the political community in question and explore the complex layers of their motivations and goals around participation. Content analysis employed in the movement's Facebook groups allows us to critically evaluate the potential of social media in (re)defining the meaning and practice of civic participation. Findings indicate that the failure of traditional forms of civic participation to attain and resolve everyday political issues becomes its potential to transfer the political activity in other sites of struggle. The role of Facebook is double: it can reinforce civic talk and debate through activists' digital story telling (around shared feelings and personal stories) significant for meaningful activist participation online and offline. Second, it can support new forms of alternative politics inspired by more participatory modes of engagement.